(untitled) (Research, Society and Development, 2022)
Infections represent one of the clinical causes with the greatest impact on health, where more serious situations in health services occur in Intensive Care Units (ICU). The analysis of cultures and the antimicrobial susceptibility of microorganisms isolated from biological samples from ICU patients are of paramount importance for the identification of serious infections. Thus, the present research aimed to detect the main bacteria found in cultures, as well as the susceptibility profile to the main antimicrobials used in the clinical practice of the hospital studied. Data referring to cultures and antibiograms of patients admitted to the ICU from January to July 2019 were considered in the study, with 143 samples of different positive cultures being analyzed, where 90.9% were from blood and their classification as to gram was 96 gram -positive, 44 gram-negative and 2 were from yeast. Regarding the prevalence and resistance of microorganisms found, Staphylococcus haemolyticus (24.47%), Staphylococcus epidermidis (20.98%), Acinetobacter baumanii (11.19%), Staphylococcus aureus (7%) and Klebsiella pneumoniae can be mentioned. (7%). In relation to the drugs that showed greater resistance, benzylpenicillin (9.94%) can be mentioned, followed by oxacillin (9.6%), erythromycin (9.37%) and clindamycin (8.91%). From this, the performance of an antibiogram is essential for the adequate choice of antibiotic therapy for patients, avoiding cross-contamination and consequently improving the patient’s quality of life, reducing costs in relation to the hospitalization time of these patients and avoiding the emergence of resistant microorganisms.